Better together: How digital connectivity and regulation reduce trade costs - Chiara Bellucci; Stela Rubínová; Roberta Piermartini (World Trade Organization (WTO), 2023)
In this paper we study the impact of digitalization on trade costs in 58 economies over the period 2014 - 2018. Improvements in digital connectivity can reduce trade costs through multiple channels, including better access to information, lower transaction costs, the reduced need for business travel, more efficient customs and logistics, and easier communication. However, these positive effects depend on effective regulation that ensures trust in digital markets and open access to digital infrastructure, services and data. We assess the impact of digital connectivity, proxied by the number of active mobile broadband subscriptions per capita, on a broad measure of trade costs that captures all impediments that make international trade more difficult or costly than domestic trade. We estimate that a 10 percentage point higher digital connectivity is associated with around 2 per cent lower trade costs both in goods and services. Digital trade regulation that ensures cross-border connectivity and information flows amplifies the trade-cost-reducing effect of improved digital connectivity. This result is particularly strong in digitally deliverable services where the marginal effect of connectivity at the best regulation is 80 per cent larger than at the median regulation.
Keywords: F10; F14; F15; 330; digital trade; trade costs; gravity model; digital regulation